Correlation of phenotypic tests with the presence of the blaZ gene for detection of beta-lactamase - Ferreira, Adriano Martison [UNESP]; Martins, Katheryne Benini [UNESP]; Silva, Vanessa Rocha da [UNESP]; Mondelli, Alessandro Lia [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (Springer Nature, 2017)
Staphylococcus aureus and Staphylococcus saprophyticus are the most common and most important staphylococcal species associated with urinary tract infections. The objective of the present study was to compare and to evaluate the accuracy of four phenotypic methods for the detection of beta-lactamase production in Staphylococcus spp. Seventy-three strains produced a halo with a diameter ≤28 mm (penicillin resistant) and all of them were positive for the blaZ gene. Among the 28 susceptible strain (halo ≥29 mm), 23 carried the blaZ gene and five did not. The zone edge test was the most sensitive (90.3%), followed by MIC determination (85.5%), but the specificity of the former was low (40.0%). The nitrocefin test was the least sensitive (28.9%). However, the nitrocefin test together with the disk diffusion method showed the highest specificity (100%). The present results demonstrated that the zone edge test was the most sensitive phenotypic test for detection of beta-lactamase, although it is still not an ideal test to detect this type of resistance since its specificity was low. However, the inhibition halo diameter of the penicillin disk can be used together with the zone edge test since the same disk is employed in the two tests. Combined analysis of the two tests shows a sensitivity of 90.3% and specificity of 100%, proving better sensitivity, especially for S. saprophyticus. This is a low-cost test of easy application and interpretation that can be used in small and medium-sized laboratories where susceptibility testing is usually performed by the disk diffusion method.
Keywords: Beta-lactamase; blaZ; Staphylococcus saprophyticus; Urinary tract infection; Zone edge test